The implications of Acemoglu and Robinson’s critical junctures and the weight of history on the Nigeria socio-political development: a philosophical analysis - Anyim Benjamin Anyim; Marygrace Enekwachi O; Jacinta Onyinyechi Oko; Omole Mayowa Samuel; Francisca Anyim-Ben (Center for Humanities and Innovation Studies, 2019)
The study focused on ‘the implications of Acemoglu and Robinson’s critical junctures and the weight of history on the Nigeria sociopolitical development: a philosophical analysis.’ The study explored the critical periods and moments of the country’s socio -political development by interpreting and interrogating events and establishing the necessary connections of such events as related to the political development of Nigeria. The study also analyzed the various critical junctures in Nigeria like the independence, the first military coup, the Nigerian-Biafra civil war, annulment of June 12 1993 general election hence its implications to the critical juncture of Nigeria socio-political development in that the most significant challenge this country has faced in every crucial juncture is the kind of leaders that emerged. They continued and consolidated on the extractive institution created by the previous leaders and have not taken it as their moral responsibility to change the trajectory of the nation. The study concluded thus, building inclusive economic and political institutions at every critical juncture is an economic transformation answer for Nigeria’s socio-political development and human flourishing everywhere in the country and at all times. Finally, the study recommended that ‘inclusive institutions’ are akin and pivotal for the realization of prosperity and human thriving.